Self-Distributing Systems in the Wild: An Experimental Study on a Real-world Edge-Cloud Continuum Platform - Naspolini, Matheus Ávila; Panisson, Alison R.; Lau, Jim; Vigil, Martín; Bittencourt, Luiz F.; Rodrigues-Filho, Roberto (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Contemporary distributed applications must often simultaneously satisfy low-latency requirements and high computational demand in order to deliver high Quality of Experience to end users. The edge–cloud continuum has emerged as a promising infrastructure paradigm to address these requirements by combining proximity to users at the edge with the abundant computing resources of the cloud. However, despite this infrastructural potential, service-level mechanisms capable of jointly exploiting network and computing resources remain limited, as these dimensions are often managed independently. To address this gap, the concept of self-distributing systems (SDS) has been proposed, enabling applications originally designed for local execution to autonomously spread themselves across distributed infrastructures at runtime. By dynamically relocating and replicating components, SDS facilitate the simultaneous exploitation of low-latency edge resources and high-performance cloud resources. Nevertheless, the practical integration of SDS with modern deployment and orchestration environments is still unexplored. This paper presents SDS_SWARM, an architecture that integrates the SDS paradigm with Docker and Docker Swarm for real-world edge and cloud infrastructures. We evaluate the architecture using a CPU-intensive service to assess its adaptive capabilities. Experimental results demonstrate improved adaptability across heterogeneous environments, validating the feasibility and benefits of combining self-distributing systems with modern edge–cloud technologies.